Galactomanana de Delonix regia aumenta a expressão de citocinas e estresse oxidativo em células humanas de Adenocarcinoma ductal pancreático in vitro - Guimarães, Myleide Bizerra (2024)
Pancreatic ductal adenocarcinoma (PDAC) represents 90% of malignant neoplasms of the pancreas. Around 80% of patients have advanced or metastatic disease and the tumors have mechanisms of multiresistance to currently used chemotherapy drugs. The challenges in treating PDAC reinforce the need to search for new molecules with antitumor potential. Galactomannan extracted from Delonix regia seeds (GM-DR) has a cytotoxic effect on human PDAC cells. However, it has not yet been clarified how GMDR interacts with these cells and whether there are repercussions on the inflammatory profile and redox status of cancer cells. In this work, we investigated the effect of GMDR on the expression of pro-inflammatory mediators and oxidative stress in 2 PDAC cell lines in vitro. After treating BxPC-3 and PANC-1 cells with GM-DR (700 μg/ml) for 24h, the expression of pro-inflammatory mediators was evaluated by Western Blot (IL1β, IL6, TNF-α, NF-κB p65, COX-2). We also evaluated indirect markers of oxidative stress through GSH consumption and expression of the iNOS enzyme. GMDR induced a significant increase in TNF-α, IL-1β, IL-6 only in BxPC-3 cells. GM-DR increased NF-κB p65 in PANC-1; although BxPC-3 shows higher basal levels of p65, it was expressed equally before and after experimental treatment. Different from other mediators, GM-DR decreased COX-2 expression in BxPC-3. GM-DR also increased GSH consumption in BxPC-3, but did not alter iNOS expression. We evaluated the TLR4 receptor as a potential target for interaction with PDAC cells. Although there is constitutive expression of the receptor in both lines, GM-DR increased the immunofluorescence intensity and TLR4 expression only in BxPC-3. We used molecular docking resources to evaluate the affinity of receptor-ligand complex formation between GM-DR and TLR4. We found that GM-DR has a strong binding affinity at the active site of the TLR4 receptor, and can firmly bind to the same pocket as LPS. Although we have not fully elucidated the mechanisms by which GM-DR produces intracellular biological effects on PDAC cells, the results described here suggest that GM-DR appears to activate the classical polysaccharide inflammatory response via TLR4 in BxPC-3 cells.